Intelligent Controller for Monitoring Vehicles at the Roads - Mohammed, Hussein A.; Omran, Alaa Hamza; Raheem, Ahmed; Abid, Yaser M. (Al-Nahrain Journal for Engineering Sciences, 2017)
Many mobile applications use infrared (IR) and Ultrasonic sensors for distance measurements. In this paper, these two types of sensors have been used in building obstacle detection system and the attributes of each sensor has been tested, the system consists of transmitter and receiver circuit, furthermore, Arduino UNO card has been used for transmitting and receiving signal for each type of sensor based on the Arduino software. The test was performed through distributing these sensors on the road then analyze the reflected signal. Neural network trained and used for monitoring the street and producing the number of cars in each line of street and the total number of cars in the same street.